Monetary correction: comparison of Brazilian, Argentine, and International standards (Revista Brasileira de Contabilidade e Gestão, 2013)
Considering the accounting function to present the financial position of the companies, the current stage of the convergence and the existence of inflation in capitalist economies, this paper aims to analyze the similarities and differences of Brazilian, Argentinean and international standards dealing or dealt with hyperinflation and restatement of the balance sheet, through the comparison between them. This is a comparing standards survey, which are analyzed the rules issued in Brazil and Argentina in hyperinflationary periods. It is still considered the international accounting standard in accordance with the criteria for recognition, measurement and presentation, demonstrating that the solutions adopted by the two countries were already in many respects, in accordance with international practice. The international standard requires more professional judgment, from the moment that does not stipulate specific rules and it is guided by general principles. The Brazilian and Argentine standards are more detailed, bringing a higher level of rules, as stipulated indexers and specific forms and specific criteria for each financial statement. Although there is no longer regarded as an environment of hyperinflation in Brazil, the study of treatments normative data for inflation is important that while there is still the presence of annual inflation, the effects of which are not recognized in the financial statements of companies. Moreover, the knowledge and the exchange of international experiences regarding the regulation of the issue and bring benefit to science development.
Keywords: standardization; restatement of balance; Brazil; Argentina; inflation